The problem of ambidexterity in the context of internationalization - Mazur, Karolina (Problem ambidexterity w kontekście internacjonalizacji, 2018)
The paper refers to the problem of ambidexterity in the international context. The purpose of this paper is to examine how ambidexterity enhances the process of innovation in international business. The problem has been analysed with the application of organizational performance measures including economic performance, innovation performance and international performance. The author used a systematic review of the literature as a research tool. The research was conducted based on the papers included in the international databases contained in international and domestic research papers. The tests included six digital databases (EBSCO, PROQUEST, ELSEVIER, EMERALD, JSTOR and WILEY) with most of the digital publications including words: “internationalization”, “innovation” and “ambidexterity”. The main research result was thus identified. The set of 19 research studies was the object of analysis. The author presented the general limitations of the research studies which created the possibilities of future projects’ development
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 4 (50), s. 94-107
Keywords: innovation; ambidexterity; internationalization; performance; innowacje; internacjonalizacja; sprawność